Getting Away With Murder: An Examination of Detected Homicides Staged as Suicides. (February 2016) - Ferguson, Claire; Petherick, Wayne
Staged crime scenes involve an offender deliberately altering evidence to simulate events to mislead investigators. Despite likely occurring more often than reported in the literature due to success in offender deception, the exact frequency of staged crime scenes is unknown. In an attempt to bridge this gap, a legal database was searched for detected staged scenes. A total of 115 cases were examined, and this study reports on 16 staged suicides that were examined through descriptive analysis. Findings indicate the frequent involvement of firearms, hanging, or asphyxia, and that offenders are usually known to victims, although not necessarily intimately.